Ultrasound and Ankle Theraband Exercise for Grade 1 Dextra Ankle Sprain Rehabilitation - Yunika Putri Alifiah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to determine the effectiveness of physiotherapy management using ultrasound (US) modality and ankle theraband exercise in reducing pain, increasing joint range of motion, improving muscle strength, and restoring functional mobility in patients with grade 1 dextra ankle sprain. Methodology: This study used a descriptive case study method involving one patient with grade 1 dextra ankle sprain. Physiotherapy interventions included Ultrasound (US) modality and Ankle Theraband Exercise conducted in three therapy sessions. Evaluation instruments consisted of Visual Analog Scale (VAS), goniometer for joint range of motion assessment, and Manual Muscle Testing (MMT) for muscle strength evaluation. Main Findings: The findings showed a significant reduction in pain intensity, including tenderness, movement pain, and resting pain after three therapy sessions. Joint range of motion in the ankle increased progressively in sagittal and frontal movements. Muscle strength in flexor and inversor muscles also improved following intervention. Ultrasound and ankle theraband exercise effectively enhanced joint mobility, reduced pain, and increased muscle strength in grade 1 dextra ankle sprain patients. Novelty/Originality of this study: This study provides practical evidence regarding the combined application of Ultrasound (US) modality and Ankle Theraband Exercise in managing grade 1 dextra ankle sprain. The originality of this research lies in integrating therapeutic exercise and physical modality interventions to simultaneously improve pain reduction, joint mobility, and muscle strength within a short physiotherapy treatment period